Assessing the Social-Emotional Development of Children Aged 4-6 Years - Hidayat, Sandra Taufik; Beni, Herman (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2024)
ABSTRACT Social emotional assessment in early childhood is a series of data and information collection processes carried out to determine the development of children and plan stimulation that will be carried out by teachers in subsequent learning. This study aims to analyze the social emotional abilities of children aged 4-6 years, especially in the social emotional aspect. This study was conducted in 3 PAUD units involving 90 students. This study uses a qualitative method carried out in two stages, namely conducting a preliminary study and conducting observation activities. Data collection techniques use observation, interviews and documentation which are used to strengthen and support the completeness of the research data. Data analysis techniques use descriptive analysis with stages of data collection, data reduction, data presentation and drawing conclusions assisted by percentage analysis. The results of the study showed that 72% of children aged 4-6 years in PAUD units have shown good social emotional abilities. This can be seen from independence, discipline, showing self-confidence, prosocial attitudes, being responsible, interacting with peers and adults, sharing, helping and assisting fellow friends. The findings show that teachers have stimulated children through daily habits through planned habits. In addition, the PAUD unit communicates with parents so that good habits are also carried out at home. Keywords: Assessment, social emotional, early childhood ABSTRAK Asesmen sosial emosional pada anak usia dini merupakan suatu rangkaian proses pengumpulan data dan informasi yang dilakukan untuk mengetahui perkembangan anak dan merencanakan stimulasi yang akan dilakukan oleh guru pada pembelajaran selanjutnya. Penelitian ini bertujuan untuk menganalisis kemampuan sosial emosional anak usia 4-6 tahun khususnya pada aspek sosial emosional. Penelitian ini dilakukan di 3 satuan PAUD yang melibatkan 90 peserta didik. Penelitian ini menggunakan metode kualitatif yang dilakukan dalam dua tahapan yakni melakukan studi pendahuluan dan melakukan kegiatan observasi. Teknik pengumpulan data menggunakan observsi, wawancara dan dokumentasi yang digunakan untuk menguatkan dan mendukung kelengkapan data hasil penelitian. Teknik analisis data menggunakan analisis deskriptif dengan tahapan pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan dibantu dengan analisis prosentase. Hasil penelitian menunjukan bahwa 72% anak usia 4-6 tahun di satuan PAUD telah menunjukan kemampuan sosial emosional yang baik. Hal ini terlihat dari kemandirian, kedisiplinan, menunjukkan rasa percaya diri, sikap prososial, bertanggung jawab, berinteraksi dengan teman sebaya dan orang dewasa, berbagi, menolong dan membantu sesama teman. Temuan menunjukan bahwa guru telah menstimulasi anak melalui pembiasaan setiap hari melalui pembiasaan yang terencana. Selain itu satuan PAUD melakukan komunikasi dengan orangtua sehingga pembiasaan baik juga dilakukan di rumah. Kata Kunci: Assessment, sosial emosional, anak usia dini